2014
DOI: 10.7566/jpsj.83.053704
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of High-Tc Phase of BiS2-Based Superconductor LaO0.5F0.5BiS2 Using High-Pressure Synthesis

Abstract: High-quality polycrystalline samples of LaO0.5F0.5BiS2 were obtained using high-pressure synthesis technique. The LaO0.5F0.5BiS2 sample prepared by heating at 700 ºC under 2 GPa showed superconductivity with superconducting transition temperatures (Tc) of Tc onset = 11.1 and Tc zero = 8.5 K in the electrical resistivity measurements and Tc onset = 11.5 and Tc irr = 9.4 K in the magnetic susceptibility measurements, which are obviously higher than those of the LaO0.5F0.5BiS2 polycrystalline samples obtained usi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
56
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 63 publications
(62 citation statements)
references
References 19 publications
5
56
1
Order By: Relevance
“…The partial substitution of O by F is useful for this carrier doping. Although, optimal fluorine concentration is estimated to be around x = 0.5, the obtained superconducting transition temperature (T c ) is completely different between conventional solid state reactions and high pressure synthesis [2,[13][14][15]. In the case of the conventional solid state reaction, the T c of LaO 0.5 F 0.5 BiS 2 is obtained at only 3 K. On the other hand, the T c largely increases above 10 K by using high pressure synthesis.…”
Section: Introductionmentioning
confidence: 95%
“…The partial substitution of O by F is useful for this carrier doping. Although, optimal fluorine concentration is estimated to be around x = 0.5, the obtained superconducting transition temperature (T c ) is completely different between conventional solid state reactions and high pressure synthesis [2,[13][14][15]. In the case of the conventional solid state reaction, the T c of LaO 0.5 F 0.5 BiS 2 is obtained at only 3 K. On the other hand, the T c largely increases above 10 K by using high pressure synthesis.…”
Section: Introductionmentioning
confidence: 95%
“…One-step high-pressure synthesis can also provide a higher-T c phase of LaO 0.5 F 0.5 BiS 2 under the optimal synthesis condition of 2 GPa and 700 ºC [24]. Crystal structure analysis revealed that the higher-T c phase of LaO 0.5 F 0.5 BiS 2 can be induced by uniaxial lattice contraction along the c axis [25]. Furthermore, Tomita et al reported that the lattice contraction under high pressure could be explained by a structural transition from tetragonal to monoclinic on the basis of analysis of the x-ray diffraction patterns under high pressure and optimization of the atomic positions by using density functional theory calculations [23].…”
Section: Introductionmentioning
confidence: 99%
“…Tc of ~10 K [2,[16][17][18]. The emergence of bulk superconductivity and increase of Tc in the highpressure phase can be attributed to the structural phase transition from the tetragonal low-Tc phase to the monoclinic high-Tc phase [13].…”
mentioning
confidence: 99%